Design, implementation and assessment of a health education service on the correct use of drugs in a pediatric Mexican hospital - Rivera S; Lopez Orozco M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
A Service of Health Education was implemented, in a Mexican Pediatric Hospital (Hospital del Niño DIF-Hidalgo), as dependent service of the Hospital Pharmacy Services, being the main objective of the service to provide independent, up-to-date and evaluated information in a simple, clear, concise and precise format, on the Correct Use of the Medications to the parents or tutors of the patient, family and to the community in general. Comparing the patient parents 'or tutors' awareness, before and after an educational session pharmacist provided carried out the evaluation of the Service. The evaluation was made, through two interviews to 270 parents or tutors. The interview measured the patient knowledge about: 1) illness, 2) the medication definition and adverse effects, 3) pharmacological and not pharmacological treatment. The study demonstrated that the parents or tutors significantly increased the knowledge on the illness and the patients' therapy, after receiving health education (p <0.001).